2022
DOI: 10.1128/spectrum.02478-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of a Novel Hydrophobic Protein VdHP1 from Verticillium dahliae

Abstract: Verticillium dahliae is a soilborne fungal pathogen that causes a destructive vascular disease on a large number of plant hosts, resulting in great threat to agricultural production. In this study, it was illustrated that the hydrophobin VdHP1 could induce cell death and activate plant immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 82 publications
(102 reference statements)
1
20
0
Order By: Relevance
“…Concomitant with impaired dispersal, scanning electron microscopy analysis of the Δ sep and Δ hfbA mutants showed a morphological change in spores and conidiophore structure compared to the control ( Fig. 5 ), as has been reported in studies of other fungi ( 5 , 28 ). It is likely that structural changes in Δ sep and Δ hfbA spores contributed to the reduced dispersion.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Concomitant with impaired dispersal, scanning electron microscopy analysis of the Δ sep and Δ hfbA mutants showed a morphological change in spores and conidiophore structure compared to the control ( Fig. 5 ), as has been reported in studies of other fungi ( 5 , 28 ). It is likely that structural changes in Δ sep and Δ hfbA spores contributed to the reduced dispersion.…”
Section: Discussionsupporting
confidence: 78%
“…Our greatest interest was assessing the fitness of the Δ sep mutant in host colonization because several hydrophobin mutants have been reported as being less virulent than other plant-pathogenic fungi, including F. graminearum , M. oryzae , Ophiostoma novo-ulmi , Verticillium dahliae , and Cryphonectria parasitica ( 7 , 8 , 14 , 28 , 29 ). The most powerful method for assessing the fitness of different fungal strains is through competition experiments ( 30 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is particularly important to study the molecular mechanism of V. dahliae and host plants. In previous studies, knockout of FgERG4 in F. graminearum led to a decline in conidial production and malformation of conidia (Liu, et al 2013), knockout of VdHP1 in V. dahliae reduces conidial smoothness (Zhang, et al 2022a). In this study, it was found that the knockout of VdERG2 led to the decrease of conidial yield and conidial germination rate, and abnormal conidial morphology (Figure 2).…”
Section: Discussionmentioning
confidence: 88%
“…For the determination of abiotic stress, 1 mol/L KCl, 1 mol/L NaCl, 1 mol/L Sorbitol, 0.004% SDS and 0.02% CR were added to PDA medium (Liu, et al 2021a, Zhang, et al 2022a). Normal PDA medium was used as a control.…”
Section: Stress Response and Carbon Utilization Detectionmentioning
confidence: 99%
See 1 more Smart Citation